2016
DOI: 10.1021/acssuschemeng.6b00604
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Silica-Supported Peroxycarboxylic Acid for the Epoxidation of Unsaturated Fatty Acid Methyl Esters and Vegetable Oils

Abstract: A silica-supported peroxycarboxylic acid oxidant, 2-percarboxyethyl silica (SiO2@(CH2)2COOOH), was successfully prepared and used for the epoxidation of fatty acid methyl esters (FAMEs) and vegetable oils. Among the oxidants prepared under different conditions, C-SiO2@(CH2)2COOOH (TEOS:CTES = 2:1) had the highest surface area, pore volume, and peroxide value. It also exhibited the highest activity for the epoxidation reactions. For methyl linoleate, 92.76% yield of epoxidized product was obtained at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“… 2 , 3 However, various energy policies in different countries that encourage the use of electric vehicles to lower the demand for biodiesel suppressed the demand for FAME. Hence, the epoxidation reaction can be the solution towards the utilization of the FAME producing higher-value chemicals, especially, epoxide products 4 which are used in as plasticizers 5 , stabilizer in PVC, intermediates in polyurethane polyols 6 , lubricants 7 , cosmetics, precursors of various polymer 8 , wood impregnation, biofuel additives 9 , and in pharmaceuticals 10 . So far, the low-temperature liquid-phase epoxidation reaction was described by Prileshajew, as shown in Supplementary Figures S1 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 However, various energy policies in different countries that encourage the use of electric vehicles to lower the demand for biodiesel suppressed the demand for FAME. Hence, the epoxidation reaction can be the solution towards the utilization of the FAME producing higher-value chemicals, especially, epoxide products 4 which are used in as plasticizers 5 , stabilizer in PVC, intermediates in polyurethane polyols 6 , lubricants 7 , cosmetics, precursors of various polymer 8 , wood impregnation, biofuel additives 9 , and in pharmaceuticals 10 . So far, the low-temperature liquid-phase epoxidation reaction was described by Prileshajew, as shown in Supplementary Figures S1 .…”
Section: Introductionmentioning
confidence: 99%
“…Table gives the comparison of IV C of various oils for different types of catalysts including homogeneous, heterogeneous (polymeric and metallic) catalysts that are reported in the literature . In the present work, all the experiments were conducted for a limited period to show the dependent variables effect on the IV C .…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of homogeneous molybdenum catalyst per reaction was only 1 %. Another work, by Benaniba et al is comparable because they also used a tungsten‐based catalyst for sunflower oil epoxidation and reported a promising result after 8 h. Recent development of organometallic oxidant by Yao et al showed the performance in peroxidation of olive oil and linseed oil. They reported a high conversion, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations